Regulation of the Nuclear Factor (NF)-.KAPPA.B Pathway by ISGylation - Minakawa, Miki; Sone, Takayuki; Takeuchi, Tomoharu; Yokosawa, Hideyoshi (Biological & pharmaceutical bulletin, 2008)
Post-translational modification with ISG15 (interferon-stimulated gene 15 kDa) (ISGylation) is mediated by a sequential reaction similar to ubiquitination, and various target proteins for ISGylation have been identified. We previously reported that ISGylation of the E2 ubiquitin-conjugating enzyme Ubc13 suppresses its E2 activity. Ubc13 forms a heterodimer with Uev1A, a ubiquitin-conjugating enzyme variant, and the Ubc13-Uev1A complex catalyzes the assembly of a Lys63-linked polyubiquitin chain, which plays a non-proteolytic role in the nuclear factor (NF)-kappaB pathway. In this study, we examined the effect of ISGylation on tumor necrosis factor receptor-associated factor (TRAF)-6/transforming growth factor beta-activated kinase (TAK)-1-dependent NF-kappaB activation. We found that expression of the ISGylation system suppresses NF-kappaB activation via TRAF6 and TAK1 and that the level of polyubiquitinated TRAF6 is reduced by expression of the ISGylation system. Taken together, the results suggest that the NF-kappaB pathway is negatively regulated by ISGylation.